Plasma-induced black bismuth tungstate as a photon harvester for photocatalytic carbon dioxide conversion. (13th January 2021) - Zhong, Kang; Zhou, Anqi; Zhou, Guli; Li, Qidi; Yang, Jinman; Wang, Zhaolong; Zhu, Xingwang; Qian, Junchao; Hua, Yingjie; Li, Huaming; Xu, Hui
Abstract : The Bi QDs are reduced in situ on the surface of black Bi2 WO6 nanosheets using a novel plasma treatment, which shows a superior CO2 conversion performance. Abstract : The photocatalytic conversion of carbon dioxide into fuels and valuable chemicals is a promising avenue to address the challenge of environmental change. Plasma treatment as a popular and effective method to prepare and modify materials based on its ultra-high energy and efficiency has attracted significant attention. In this study, abundant Bi quantum dots (Bi QDs) are reduced in situ on the surface of black Bi2 WO6 nanosheets using an effective dielectric barrier discharge (DBD) plasma technology. The reduction of Bi QDs leads to the generation of a large number of unsaturated coordination atoms, which improves the light absorption performance of Bi2 WO6 . Benefiting from the unique interface design, black Bi2 WO6 shows superior CO generation rate, roughly threefold higher than that of pristine Bi2 WO6 nanosheets. Our work provides new insights and can be a reference in plasma modification engineering of catalyst surfaces and photoreduction of CO2 .